2021
DOI: 10.3390/ijerph18041929
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Thyroid Functions among Female Flight Attendants

Abstract: Introduction: Epidemiological observations indicate that stewardesses are exposed to reproductive and endocrine system disturbances. The aim of the study was to assess of thyroid function disturbances as well as to identify factors affecting the thyroid function among stewardesses working both within one time zone and on long-distance flights. Material and methods: The cross-sectional study covered 103 women aged 23–46. The study group (I) was divided into two subgroups: group Ia comprising stewardesses flying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This finding was in agreement with Kuetting et al 18 In the current study, the mean FT 4 level of both groups was within the normal range but somewhat lower in the study group than that in the control group. A similar type of observation was also found by Radowicka et al 19 They concluded that autoantibodies against thyroid peroxidase and thyroglobulin developed in night-shift workers decrease thyroid hormone synthesis. As a result, serum FT 4 levels decrease.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was in agreement with Kuetting et al 18 In the current study, the mean FT 4 level of both groups was within the normal range but somewhat lower in the study group than that in the control group. A similar type of observation was also found by Radowicka et al 19 They concluded that autoantibodies against thyroid peroxidase and thyroglobulin developed in night-shift workers decrease thyroid hormone synthesis. As a result, serum FT 4 levels decrease.…”
Section: Discussionsupporting
confidence: 81%
“…A similar type of observation was also found by other researchers. 5,7,17,19 In their study, it was found that the TSH level in night shift workers was significantly higher than that in the morning shift workers. The circadian system regulates all physiological processes that are modulated by changes in the external environment light exposure and food intake.…”
Section: Original Articlementioning
confidence: 90%